Contrasting Patterns in Abrupt Asian Summer Monsoon Changes in the Last Glacial Period and the Holocene. Issue 2 (24th February 2018) - Liu, Dianbing; Wang, Yongjin; Cheng, Hai; Edwards, R. L.; Kong, Xinggong; Chen, Shitao; Liu, Shushuang
Abstract: Detailed Asian summer monsoon (ASM) variability across Heinrich stadials (HSs) 5 to 2 was reconstructed from four stalagmite oxygen isotopic (δ 18 O) records in central and southern China. For the last glacial period, these speleothem records, combined with previous cave records, reveal a rapid ASM decline at the onset of each HS. During this time, ASM intensity decreases immediately to the weakest level within approximately 50 years, which is followed by a gradual intensification in the mid‐HS. Typically, this process of ASM weakening is synchronous with peak ice‐rafted debris deposition and large freshwater outbursts into the North Atlantic, implying a tight link between the two. During the Holocene, however, a relatively gradual ASM decrease occurred at the start of the Bond events. Comparatively, the ASM decrease during the Bond events is generally accomplished within 110 years, and the weakest ASM occurs near the end. This difference implicates a further southward displacement of the Intertropical Convergence Zone and a stronger impact from the Atlantic meridional overturning circulation on the ASM in the early HS. Moreover, contrasting expressions of the ASM during HSs and Bond events suggest that a fixed phase relationship during bipolar climate changes cannot be expected. Plain Language Summary: The anatomy of internal structures in abrupt climate events under different climate boundaries is important for understanding the physical mechanisms. The δ 18 O records from Chinese cave deposits can be used as an indicator for Asian summer monsoon (ASM) variability, which is closely related to changes of North Atlantic climates and shifts of the Intertropical Convergence Zone. In this study, a comparison of δ 18 O records from different caves in China revealed that the ASM declined rapidly at the onset of the Heinrich events in the last glacial period but gradually at the onset of Bond events in the Holocene. This indicates that the volume of freshwater inputs into the North Atlantic during the Heinrich events was large, and the southerly movement of the Intertropical Convergence Zone was exceptionally significant. As an atmospheric bridge linking bipolar climate changes, different expressions in ASM variations in the last glacial and the Holocene should be considered when correlating northern and southern hemispheric climate changes. Key Points: Detailed speleothem‐based ASM variability across HS 5 through 2 Contrasting patterns of HS (rapid onset) and Bond events (gradual onset) Insights into dynamics of abrupt climate changes under different boundaries